Free speech and loss in white nationalist rhetoric. Issue 2 (2nd July 2020) - Chebrolu, E.
ABSTRACT: This article analyses how anti-blackness structures the desire for free speech within white nationalist ideology. The essay traces the linkages between the rhetoric of a mission statement for a white nationalist webzine edited by a professor of psychology and that professor's published academic work on ethnic identity. The central argument of the essay is that taken together, these texts construct an antisemitic fantasy of a crisis in free speech, in which free speech is an object of desire because of its promise to recuperate a loss rendered unto the white nation, anchored by an attachment to the anti-black bio-evolutionary origin myth of humanness.